Two new species of Aphlugiolopsis (Orthoptera: Tettigoniidae: Meconematinae) from China - Pan, Yangyang; Bian, Xun (Zootaxa, 2023)
This paper describes two new species of Aphlugiolopsis from Guangxi and Yunnan, China, based on the specimens deposited in Guangxi Normal University. Illustrations of the two new species are provided.